Why do sparkles make a sound in English? : the impact of media exposure on child L2 vocabulary acquisition - Hendrih, Mateja (Array, 2019)
Due to their features of multi-modal presentation and their abundance in terms of availability and diversity, the media have been assumed to have a distinct effect on second language acquisition (SLA). Although their beneficial effect on overall SLA has been found in various studies, very few of them examined the characteristics of different types of media in relation to how they may influence second language (L2) vocabulary acquisition at an early age. We present a case study of a 9-year-old Croatian girl who had achieved high competence in the English language primarily through exposure to television (TV) content in English. We examined her production for the evidence that some features of television as a medium might have influenced the development of her vocabulary and the way she experienced and used the L2. The production data was collected in a series of unstructured conversations in the informal atmosphere of the participant’s home. Additional data on the participant’s language learning background were collected in interviews with the participant and her parents. The results suggest that exposure to TV as a medium, which provides opportunities for repeated exposure to rich input, contextualized language, and a combination of visual and aural stimuli, may have an important influence on L2 vocabulary acquisition. However, it has to be emphasized that the influence was evidenced in the production of a highly motivated language learner in an environment that was truly supportive of her language development.